2000
DOI: 10.1097/00007890-200006150-00028
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Transplantation Free Time by Lamivudine in Patients With Hepatitis B-Induced Decompensated Cirrhosis

Abstract: The administration of lamivudine for pretransplantation HBV suppression was associated with impressive clinical and biochemical improvement. Lamivudine may extend the transplantation free time in such patients. The mechanism of this desirable effect should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The safety and efficacy of lamivudine has been evaluated in transplant patients with end‐stage liver disease caused by chronic HBV infection [20–22]. In the present study, lamivudine administration before transplantation (group 1) extended the transplantation‐free time in two patients, served as a bridge to OLT, and led to clearance of HBV from serum in all patients, thereby enabling nine of them to undergo OLT.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The safety and efficacy of lamivudine has been evaluated in transplant patients with end‐stage liver disease caused by chronic HBV infection [20–22]. In the present study, lamivudine administration before transplantation (group 1) extended the transplantation‐free time in two patients, served as a bridge to OLT, and led to clearance of HBV from serum in all patients, thereby enabling nine of them to undergo OLT.…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study [21], our group found that the administration of lamivudine in patients with active viral replication before transplantation suppressed HBV replication and induced clinical and biochemical improvement, extending the transplantation‐free time. Accordingly, others [22, 23] noted an improvement in Child–Pugh–Turcot scores in 69% of patients with HBV infection treated with lamivudine; 38% were placed on inactive status for liver transplantation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis with LAM is also effective in preventing recurrent HBV infection and graft reinfection after transplantation, although the emergence of YMDD‐variant HBV may occur 8,9 , 12–14 . Most patients still continue to benefit from LAM treatment even after the emergence of YMDD‐variant HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that LAM can improve and stabilize some patients with end‐stage liver disease, leading to increased pre‐transplant survival as well as a reduced need for transplantation 7–9 . However, the data for the efficacy of long‐term LAM therapy in patients with decompensated liver disease associated with viral replication, liver function and safety profile are limited to date.…”
Section: Introductionmentioning
confidence: 99%
“…Other interventions that may have prolonged transplant-free survival (e.g., TIPS, use of prophylactic antibiotics) may have contributed to the observed improvements in clinical outcomes. In spite of all these inadequacies, lamivudine was found to be safe in patients with decompensated HBV cirrhosis although not all patients benefited from it [67]. Clinical improvement usually occurs between 3 to 6 months of therapy and improvement might not occur if treatment is started late.…”
Section: Lamivudinementioning
confidence: 99%